PENGEMBANGAN DESAIN SISTEM BEJANA BERTEKANAN UNTUK MENINGKATKAN EFISIENSI DAN KUALITAS PRODUK PEMINDANGAN - Nitya Santhiarsa; Suarnadwipa Suarnadwipa (Buletin Udayana Mengabdi, 2010)
Production process of boiled [of] sea fish still uses the traditional technology ( boiled with the opened vessel).The business of boiled fish in Kusamba increases quite a lot although it is still traditionally applied. It is the consequence required by effort of development of design system of boiled with the pressure vessel system. System of boiled with the pressure vessel to yield the thrift energy of equal to 25 % compared to by application of boiled standard for the capacities of same and poaching temperature increase to 30? C. The application of boiled with pressure vessel compared to the opened vessel was more effective.